Effect of Peer Health Workers on AIDS Care in Rakai, Uganda: A Cluster-Randomized Trial - Chang, Larry W.; Kagaayi, Joseph; Nakigozi, Gertrude; Ssempijja, Victor; Packer, Arnold H.; Serwadda, David; Quinn, Thomas C.; Gray, Ronald H.; Bollinger, Robert C.; Reynolds, Steven J. (PloS one, 2010)
Human resource limitations are a challenge to the delivery of antiretroviral therapy (ART) in low-resource settings. We conducted a cluster randomized trial to assess the effect of community-based peer health workers (PHW) on AIDS care of adults in Rakai, Uganda. Methodology/Principal Findings: 15 AIDS clinics were randomized 2:1 to receive the PHW intervention (n = 10) or control (n = 5). PHWtasks included clinic and home-based provision of counseling, clinical, adherence to ART, and social support. Primary outcomes were adherence and cumulative risk of virologic failure (.400 copies/mL). Secondary outcomes were virologic failure at each 24 week time point up to 192 weeks of ART. Analysis was by intention to treat. FromMay 2006 to July 2008, 1336 patients were followed. 444 (33%) of these patients were already on ART at the start of the study. No significant differences were found in lack of adherence (,95% pill count adherence risk ratio [RR] 0.55, 95% confidence interval [CI] 0.23–1.35; ,100% adherence RR 1.10, 95% CI 0.94–1.30), cumulative risk of virologic failure (RR 0.81, 95% CI 0.61–1.08) or in shorter-term virologic outcomes (24 week virologic failure RR 0.93, 95% CI 0.65–1.32; 48 week, RR 0.83, 95% CI 0.47–1.48; 72 week, RR 0.81, 95% CI 0.44–1.49). However, virologic failure rates$96 weeks into ART were significantly decreased in the intervention armcompared to the control arm (96 week failure RR 0.50, 95% CI 0.31–0.81; 120 week, RR 0.59, 95% CI 0.22–1.60; 144 week, RR 0.39, 95% CI 0.16–0.95; 168 week, RR 0.30, 95% CI 0.097–0.92; 192 week, RR 0.067, 95% CI 0.0065–0.71). Conclusions/Significance: A PHW intervention was associated with decreased virologic failure rates occurring 96 weeks and longer into ART, but did not affect cumulative risk of virologic failure, adherence measures, or shorter-term virologic outcomes. PHWs may be an effective intervention to sustain long-term ART in low-resource settings
Keywords: Peer Health Workers; AIDS Care; Rakai